Prognostic Value of Procalcitonin and Procalcitonin Clearance in Septic Shock Patients: A Study from a Tertiary Teaching Hospital in Southern China - Liu Y; Zhao S; Qin Z; Huang X (Infection and Drug Resistance)
Yao Liu,1 Shuangping Zhao,2 Zixi Qin,3 Xun Huang3 1Department of Hepatopathy, The Hunan Provincial People’s Hospital, The First Affiliated Hospital of Hunan Normal University, Changsha, People’s Republic of China; 2Department of Critical Care Medicine, Xiangya Hospital, Central South University, Changsha, People’s Republic of China; 3Department of Infection Control Center, Xiangya Hospital, Central South University, Changsha, People’s Republic of ChinaCorrespondence: Xun Huang, Department of Infection Control Center, Xiangya Hospital, Central South University, Changsha, People’s Republic of China, Email huangxun@mail.csu.edu.cnObjective: This study aimed to evaluate the potential prognostic value of procalcitonin (PCT) and procalcitonin clearance (PCTc) among patients with septic shock.Methods: We conducted a prospective single-center observational study of septic shock patients admitted to the adult intensive care unit (ICU) of a tertiary teaching hospital in Southern China between January and December 2015. Serum PCT levels of surviving patients were measured at the onset of septic shock and subsequently on days 2 (24 h), 3 (48 h), 4 (72 h), and 5 (96 h), respectively. Similarly, PCTc on Days 2, 3, 4, and 5 were calculated to evaluate their prognostic performance.Results: One hundred and twenty-eight adult patients with septic shock were included in the study. There was no significant difference between PCT concentrations measured at a single time point in survivors and non-survivors. However, PCTc on Day 2, 3, and 5 were significantly higher in survivors than in non-survivors. The best area under the receiver operating characteristic curve (AUC) values for prognosis were 0.74 (95% CI, 0.59– 0.88), 0.74 (95% CI, 0.61– 0.86), and 0.72 (95% CI, 0.54– 0.90), respectively. In the logistic regression analysis, PCTc-day 2 > 12.7% and PCTc-day 3 > 49.6% were identified as independent predictors of survival for patients with septic shock. However, PCTc-day 5 was not independently associated with survival. The best cutoff for PCTc-day 2 and day 3 were 12.7% and 49.6%, respectively.Conclusion: Compared with PCTc, PCT demonstrated lower prognostic performance for the survival of patients with septic shock. However, PCTc on Day 2 and 3 were significantly associated with survival in patients with septic shock and may serve as valuable prognostic indicators.Keywords: procalcitonin, procalcitonin clearance, septic shock, prognosis, biomarker